2011
DOI: 10.1007/s12602-011-9070-y
|View full text |Cite|
|
Sign up to set email alerts
|

Biopreservation of Sardinella longiceps and Penaeus monodon Using Protective Culture Streptococcus phocae PI 80 Isolated from Marine Shrimp Penaeus indicus

Abstract: The influence of Streptococcus phocae PI80 on the shelf life of Sardinella longiceps and Penaeus monodon was investigated by measurement of microbial and chemical analysis after appraising the safety of the protective probiotic culture in wistar rat's model. The results of this safety assessment indicate that oral administration of protective culture does not demonstrate any toxicological effects. Consumption of this LAB strain had no adverse effects on animal's general health status, hematology, blood biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The increase in TVB-N in sardine fillets is directly associated with proteolysis and degradation of nitrogenous and volatile compounds by spoilage microorganisms [42,43]. The use of OV50 significantly reduced the TVB-N level in fresh sardines, which is consistent with previously reported data [44,45]. OV50's ability to reduce TVB-N levels in fresh sardines demonstrates its effectiveness in preserving seafood quality by inhibiting protein degradation and minimizing spoilage indicators.…”
Section: Discussionsupporting
confidence: 88%
“…The increase in TVB-N in sardine fillets is directly associated with proteolysis and degradation of nitrogenous and volatile compounds by spoilage microorganisms [42,43]. The use of OV50 significantly reduced the TVB-N level in fresh sardines, which is consistent with previously reported data [44,45]. OV50's ability to reduce TVB-N levels in fresh sardines demonstrates its effectiveness in preserving seafood quality by inhibiting protein degradation and minimizing spoilage indicators.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, S. phocae PI80 was found to exhibit potent probiotic role against vibriosis in shrimp Penaeus indicus and Aeromonas infection in fishes Cyprinus carpio and Tilapia mossambicus [19,20]. Recently, Paari et al [21] reported that probiotic S. phocae PI80 could be used as a potent biopreservative agent in the preservation of Tiger shrimp Penaeus monodon. Maintenance of high viability of S. phocae PI80 is important due to the aforementioned application.…”
Section: Resultsmentioning
confidence: 99%
“…). S. phocae was isolated from Penaeus indicus (Gopalakannan ) show good probiotic characters (Sathishkumar & Arul ) and found to be safe (Paari et al ., ). We recently reported enhancement of immune response and control of vibrios by S. phocae in juvenile and adult shrimp P. monodon (Pattukumar et al .…”
Section: Introductionmentioning
confidence: 97%
“…There have been several studies that have documented the beneficial use of Streptococcus phocae PI80 in lab scale experiment which controlled the vibriosis in postlarval stage of shrimp Penaeus monodon (Swain et al 2009). S. phocae was isolated from Penaeus indicus (Gopalakannan 2006) show good probiotic characters (Sathishkumar & Arul 2009) and found to be safe (Paari et al, 2011). We recently reported enhancement of immune response and control of vibrios by S. phocae in juvenile and adult shrimp P. monodon (Pattukumar et al 2013).…”
mentioning
confidence: 99%